Supplementation with 2000 IU of Cholecalciferol Is Associated with Improvement of Trabecular Bone Mineral Density and Muscle Power in Pediatric Patients with IBD - Hradsky, Ondrej; Soucek, Ondrej; Maratova, Klara; Matyskova, Jana; Copova, Ivana; Zarubova, Kristyna; Bronsky, Jiri; Sumnik, Zdenek (Inflammatory bowel diseases, 2017)
BACKGROUND: Inflammatory bowel diseases (IBD) are associated with altered bone health and increased risk for fractures. Vitamin D deficiency is frequently found in IBD; however, the effect of vitamin D supplementation on bone health of children with IBD is poorly understood. We aimed to observe the changes in volumetric bone density and dynamic muscle functions after vitamin D substitution in a cohort of pediatric patients with IBD. METHODS: This was a prospective observational study of 55 patients (aged 5-19 years) with IBD. Bone quality was assessed using peripheral quantitative computed tomography and muscle functions by jumping mechanography at baseline and after a median of 13.8 (interquartile range, 12.0-16.0) months of daily substitution of 2000 IU of cholecalciferol. RESULTS: Median serum levels of 25-hydroxyvitamin D increased from 58 nmol/L at the baseline visit to 85 nmol/L at the last follow-up visit (P < 0.001); no signs of overdose were reported. The Z-scores of trabecular bone mineral density, cortical bone cross-sectional area, and maximal muscle power improved significantly during the follow-up period (+0.5, P = 0.001, +0.3, P = 0.002 and +0.5, P = 0.002, respectively). Cholecalciferol substitution was positively associated with trabecular bone mineral density and maximal muscle power (estimates 0.26, 95% confidence interval 0.14-0.37, P < 0.0001 and 0.60, 95% confidence interval 0.32-0.85, P < 0.0001, respectively) but not with the Strength-Strain Index or maximal muscle force (Fmax). CONCLUSIONS: We observed an improvement in bone and muscle parameters after cholecalciferol substitution in pediatric patients with IBD. Therefore, vitamin D substitution can be considered in such patients.
Keywords: inhibitory kostní resorpce; svalová síla; Bone Density Conservation Agents; Humans; trabekulární kostní tkáň; dítě; Child; cholekalciferol; Female; mladý dospělý; Inflammatory Bowel Diseases; výsledek terapie; lidé; Muscle Strength; Cholecalciferol; předškolní dítě; idiopatické střevní záněty; ženské pohlaví; Male; Adolescent; Treatment Outcome; Bone Density; potravní doplňky; kostní denzita; Dietary Supplements; Young Adult; Cancellous Bone; mužské pohlaví; prospektivní studie; Child, Preschool; mladiství; Prospective Studies